1994
DOI: 10.1016/0168-6445(94)90114-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of lactose utilization in lactic acid bacteria

Abstract: Lactose utilization is the primary function of lactic acid bacteria used in industrial dairy fermentations. The mechanism by which lactose is transported determines largely the pathway for the hydrolysis of the internalized disaccharide and the fate of the glucose and galactose moieties. Biochemical and genetic studies have indicated that lactose can be transported via phosphotransferase systems, transport systems dependent on ATP binding cassette proteins, or secondary transport systems including proton sympo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
93
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(95 citation statements)
references
References 71 publications
1
93
0
1
Order By: Relevance
“…Preliminary studies of CR and its glucose and lactose transport systems have been reported elsewhere (4,10,46), and, recently, two mechanisms controlling the expression of the lactose operon have been suggested: CR mediated by the PTS components and possibly by CcpA and induction by lactose through the antitermination protein LacT (1,15). However, detailed studies of this microorganism have been difficult because of the nearly complete absence of genetic tools.…”
mentioning
confidence: 99%
“…Preliminary studies of CR and its glucose and lactose transport systems have been reported elsewhere (4,10,46), and, recently, two mechanisms controlling the expression of the lactose operon have been suggested: CR mediated by the PTS components and possibly by CcpA and induction by lactose through the antitermination protein LacT (1,15). However, detailed studies of this microorganism have been difficult because of the nearly complete absence of genetic tools.…”
mentioning
confidence: 99%
“…Genetic studies of the metabolic pathways for lactose utilization in these gram-positive bacteria have revealed a variety of lac operons that differ from the paradigm known in E. coli (13). The thermophilic yogurt bacteria Streptococcus thermophilus and Lactobacillus bulgaricus contain a highly homologous lacSZ operon in which the ␤-galactosidase (lacZ) gene is located downstream from the lacS gene encoding a lactose permease (LacS), which belongs to the galactoside-pentosehexuronide translocators (27,41,48,49).…”
mentioning
confidence: 99%
“…In regard to sugar catabolism, the utilization of lactose is among the most studied in LAB (de Vos & Vaughan, 1994). Lactose permeases have been described in numerous LAB (Barrangou et al, 2003;Leong-Morgenthaler et al, 1991).…”
Section: Discussionmentioning
confidence: 99%